Changes in outer retinal microstructures during six month period in eyes with acute zonal occult outer retinopathy-complex. - Yoshitsugu Matsui; Hisashi Matsubara; Shinji Ueno; Yasuki Ito; Hiroko Terasaki; Mineo Kondo (PLoS ONE, 2014)
PURPOSE: To study the changes in the outer retinal microstructures during a six month period after the onset of acute zonal occult outer retinopathy (AZOOR)-complex by spectral-domain optical coherence tomography (SD-OCT). METHODS: Seventeen eyes of 17 patients with the AZOOR-complex were studied. The integrity of the external limiting membrane (ELM), ellipsoid zone (EZ; also called the inner/outer segment junction), and interdigitation zone (IDZ; also called the cone outer segment tips) were evaluated in the SD-OCT images obtained at the initial visit and at six months. The three highly reflective bands were divided into three types; continuous, discontinuous, and absent. The integrity of the outer nuclear layer (ONL) was also assessed. RESULTS: Among the three highly reflective bands, the IDZ was most altered at the initial visit and least recovered at six months. Fifteen of 17 eyes (88%) had a recovery of at least one of the three bands at six months in the retinal area where the ONL was intact, and these areas showed an improvement of visual field. Three eyes (18%) had retinal areas where the ONL was absent at the initial visit, and there was no recovery in both the retinal structures and visual fields in these areas. CONCLUSIONS: Our results indicate that more than 85% eyes with AZOOR-complex show some recovery in the microstructures of the outer retina during a six month period if the ONL is intact. We conclude that SD-OCT is a useful method to monitor the changes of the outer retinal microstructure in eyes with the AZOOR-complex.